The Evolution of the International Refugee Protection Regime - Erika Feller (Washington University Journal of Law & Policy, 2001)
A short historical perspective on the United Nations High Commissioner for Refugees (UNHCR) is followed by a review of how the international refugee protection regime has evolved over the past half century.
Keywords: Political refugees; United Nations; United Nations. Office of United Nations High Commissioner for Refugees